Development of Dryland Agriculture on Watershed Basis in Hot Arid Tropics of India: A Case Study - Bhati, T K; Goyal, R K; Daulay, H S (Annals of Arid Zone, 2016)
A study on watershed managenlent was initiated in 1986-87 at Jhannwar village (District, Jodhpur) and surveys were conducted to assess the problems, resources and potential of the area. The action plan was prepared and implemented. Farmers in the watershed area showed keen and sustained interest in adoption of improved dryland farming technologies, including sustainable land use systems. Productivity analysis of watershed area indicated considerable improvement in gross monetary returns under different cropping systems. Water harvesting, through creation of fann ponds and its recycling in agro-horticulture (Ziziplms mauritiana) system resulted in diversified production (fruit, fuel and fodder) and sustained 1.14 adult cattle wlit ha-1y(l. Development of pastures in community grazing lands increased forage production (2-3 t ha-1) over traditional methods (0.3-0.4 t ha-1 Adoption of various physical and biological land treatments in the eroded rocky catchment reduced the soil erosion and increased the groundwater recharge. the program has resulted in an overall increase in the productivity by 25-30%. Although highly location specific, such a model has high replicability in large part of arid tropics in India and elsewhere.